Environmental Management Strategy of Thai Temples Today - (ปภสฺสโร), พระครูโอภาสกิจจานุยุต (Journal of Educational Review Faculty of Education in MCU, 2018)
This article discusses temple environmental management with a strategy in operation within the scope of work accomplished with the cooperation of the internal staff and external participants. It starts from a participative policy, setting a policy based on the results of the current study, and setting a strategy in temple environmental management. This is a positive management based on the strength, achievement, and chance to success to inspire the teamwork to the goal, and at the same time, it is linked to vision, mission and goal relevant to the current social contexts of Thailand.